PENGARUH PRAKTIK MANAJEMEN SUMBER DAYA MANUSIA DAN PERSEPSI DUKUNGAN ORGANISASI TERHADAP KETERIKATAN KARYAWAN DENGAN KUALITAS KEHIDUPAN KERJA SEBAGAI VARIABEL INTERVENING - Avianto, Bambang; Derriawan; Tabroni (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2019)
This study aims to examine the effect of human resource management practices and perceptions of organizational support for employee engagement with quality of work life as intervening. The success of an organization depends on the approach taken to build human resources effectively. Employee engagement is defined as a positive, satisfying and work-related state of mind that is characterized by passion, dedication and absorption. Many factors can affect employee engagement, including the management of human resources, perceived of organization support and the quality of work life. Research subjects are employees of PT. X in Jakarta as many as 160 respondents. This study uses the SEM method through a questionnaire. The results show that two exogenous variables have a significant effect on intervening variables: (R2 = 0.92, p = 0.000), and the variable of work quality has a significant effect on employee engagement variables (R2 = 0.49, p = 0.000).